The effect of brain gymnastics and body gymnastics on improving cognitive function in the elderly: a holistic approach - Qomaru, Abdillah Zaman; Noortje Anita Kumaat; Heri Wahyudi; Roy Januardi Irawan (Pendidikan Jasmani, Kesehatan, dan Rekreasi Universitas Nahdlatul Ulama Sunan Giri, 2025)
Aging is associated with cognitive decline that affects memory, attention, and executive function, prompting interest in interventions such as Brain Gym and body gymnastics. This study employed a quantitative quasi-experimental design involving elderly participants aged 60 years and above to examine the effects of these exercises on cognitive performance using standardized assessments, including the MMSE and task-specific cognitive tests. Interventions were delivered for 20–30 minutes, three times per week, and data were analyzed using paired and independent t-tests or ANCOVA. The findings, supported by recent literature, suggest that both Brain Gym and body gymnastics may contribute to improvements in cognitive function by enhancing neural coordination and promoting better cerebral blood flow; however, considerable heterogeneity in intervention types, durations, outcomes, and study quality limits the strength of these conclusions. The evidence should therefore be interpreted cautiously, and further high-quality randomized controlled trials are needed to verify these effects. Limitations include incomplete statistical reporting in previous studies, potential publication bias, language restrictions, methodological variability, and small sample sizes across the included literature.